2012
DOI: 10.1371/journal.pone.0052255
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Testosterone, Androstenone, and Estradiol Metabolism in HepG2 Cells and Primary Culture Pig Hepatocytes and Their Effects on 17βHSD7 Gene Expression

Abstract: Steroid metabolism is important in various species. The accumulation of androgen metabolite, androstenone, in pig adipose tissue is negatively associated with pork flavor, odour and makes the meat unfit for human consumption. The 17β-hydroxysteroid dehydrogenase type 7 (17βHSD7) expressed abundantly in porcine liver, and it was previously suggested to be associated with androstenone levels. Understanding the enzymes and metabolic pathways responsible for androstenone as well as other steroids metabolism is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…For testosterone, as we all knew it was one of the most active androgens and mainly bounded to SHBG and albumin. However, only free testosterone was bioactive [35], [36]. So far we know that testosterone was with important functions of regulatory [37] and also related to many diseases, such as anemia, metabolic syndrome and the iron stage [18], [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For testosterone, as we all knew it was one of the most active androgens and mainly bounded to SHBG and albumin. However, only free testosterone was bioactive [35], [36]. So far we know that testosterone was with important functions of regulatory [37] and also related to many diseases, such as anemia, metabolic syndrome and the iron stage [18], [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, only free testosterone was bioactive [35], [36]. So far we know that testosterone was with important functions of regulatory [37] and also related to many diseases, such as anemia, metabolic syndrome and the iron stage [18], [36]. Furthermore, previous studies had also showed that the levels of total testosterone and SHBG were negatively associated with metabolic syndrome [16] while the levels of serum ferritin was in a positive association with metabolic syndrome [3].…”
Section: Discussionmentioning
confidence: 99%
“…The residue was reconstituted with 0.5 mL of acetonitrile and 0.5 mL of water and analyzed by LC-MS/MS with ESI+ ion source (API 5000, Applied Biosystems, ON, Canada). The instrument procedure follows the description 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Primary pig hepatocytes were isolated from Large White male pigs (3–5 days old) using procedure described by Chen et al [13] . The experimental protocol for using animals was approved by the Animal Ethics Committee of the China Agricultural University, Beijing, China (permission number: 2011-11-23-1).…”
Section: Methodsmentioning
confidence: 99%
“…It can be either irreversibly converted to estrogens by aromatase, or can be transformed to other active form such as dihydrotestosterone [9] . Testosterone metabolism in pig hepatocytes has been studied previously and it was established that 4-androstene-3,17-dione was its main metabolite [13] . 17β-Estradiol and dihydrotestosterone are also known as bioactive steroids of the endocrine systems.…”
Section: Introductionmentioning
confidence: 99%